Trans Fat Free by 2023—A Building Block of the COVID-19 Response - Bösch, Simone; Westerman, Lucinda; Renshaw, Nina; Pravst, Igor (Frontiers in Nutrition, 2021)
COVID-19 has brought to centre stage the most important health issue of our era, largely ignored by policymakers and the public to date: noncommunicable diseases (NCDs), the cause of 71% of deaths per year worldwide. People living with NCDs, and particularly those living with cardiovascular disease (CVD), are at higher risk of severe symptoms and death from COVID-19. As a result, the urgent need for policy measures to protect cardiovascular health is more apparent than ever. One example of ‘low-hanging fruit’ in the prevention of CVD is the elimination of industrially-produced trans fatty acids (iTFA). Their removal from the global food supply could prevent up to 17 million deaths by 2040 and would be the first time an NCD risk factor has been eliminated.